Questionnaire survey on medical care for male urethritis in community clinics in Shiga prefecture - Yamashita, Hiroto (Hinyokika kiyo. Acta urologica Japonica, 2014)
Six regional medical associations in Shiga prefecture agreed to cooperate in an investigation of medical care for male gonococcal and chlamydial urethritis. In June 2011, we sent a questionnaire to 372 medical offices in Shiga prefecture, and analyzed replies of respondents. Ten urologists and 175 non-urologists responded to the survey (response rate 49.7%). Among 185 physicians, 52 (10 urologists and 42 nonurologists) have treated male patients with gonococcal and chlamydial urethritis. More than 20% (42/175) of non-urological clinics are involved in the medical management. At initial diagnosis for sexually transmitted male urethritis, all urologists select the nucleic acid amplification method (100%), whereas many non-urologists do not (35%). For the treatment of chlamydial urethritis, non-urologists select levofloxacin (LVFX, 52.8%) rather than azithromycin (AZM, 22.0%), whereas urologists use AZM (78.0%) mostly but do not use LVFX (0%) (p = 0.023). For the treatment of gonococcal urethritis, non-urologists prefer oral new quinolones (53.1%) compared to urologists (25.0%) (p = 0. 74). For cure judgment of gonoccocal and chlamydial urethritis, many non-urologists rely on the improvement of subjective symptoms (50 and 47%), but urologists do not (10 and 0%) (p = 0.022 and 0.026, respectively). As for recognition of the clinical guideline for sexually transmitted disease, most urologists (90%) know it, but few non-urologists (13%) do (p < 0.001). We found that non-urological clinics make a great contribution to the medical treatment for male gonococcal and chlamydial urethritis in Shiga prefecture. It is important to standardize the medical care for sexually transmitted male urethritis by familiarizing non-urological practitioners with the clinical guideline